Distribution and Diversity of Ascidian in Manado Bay, North Sulawesi - Leleran, Andreas J. P. L.; Pratasik, Silvester B.; Salaki, Meiske S.; Lumingas, Lawrence J. L.; Kambey, Alex D.; Undap, Suzanne L. (Jurnal Ilmiah Platax, 2022)
The purpose of this study was to determine the distribution and the diversity of ascidians in Manado Bay including species composition, density, diversity, and dominance. This study used the quadrat transect method. This study found differences in the number of ascidian species with water depth, 11 species of 5 families at 15 M depth, and 8 species of 3 families at 7 M depth. The diversity index ranged from 0.868 to 1.844 at 15 M depth and 0.965 to 1.864 at 7 M depth, the evenness index was 0.533 – 0.839 at 15 M depth and 0.600 – 0.897 at 7 M depth, the dominance index was 0.254 – 0.745 at 15 M depth and 0.254 – 0.708 at 7 M depth. Ascidian in Manado Bay had two distribution patterns, a uniform distribution pattern and a clustered distribution pattern. Environmental parameters had a water temperature of 27 oC – 31 oC, the salinity of 30 0/00 – 32 0/00, the brightness of 12 m – 14 m, and pH of 8 – 10.*Keywords: Ascidian; diversity; ecological index; distribution patternAbstrakTujuan dari penelitian ini adalah untuk mengetahui distribusi dan keanekaragaman jenis ascidia di perairan Teluk Manado meliputi: komposisi jenis, kepadatan individu, keanekaragaman, dan dominansi. Serta mengetahui pola distribusi ascidia. Penelitian ini menggunakan metode transek kuadran. Pada penelitian ini ditemukan perbedaan jumlah spesies ascidia menurut kedalaman, 11 spesies dari 5 family pada 15 M dan 8 spesies dari 3 famili pada kedalaman 7 m. Nilai indeks keanekaragaman ascidia di kedalaman 15 m = 0.868 – 1.844 dan 7 m = 0.965 - 1.864, indeks keseragaman 15 m = 0.533 – 0.839 dan 7 m = 0.600 – 0.897, indeks Dominasi15 m = 0.254 – 0.745 dan 7 m = 0.254 – 0.708. Ascdia di perairan Teluk Manado memiliki dua pola distribusi yaitu pola distribusi seragam dan pola distribusi mengelopok. Parameter lingkungan memiliki suhu air 27 oC – 31 oC, salinitas 30 0/00 – 32 0/00, kecerahan 12 m – 14 m, dan pH 8 – 10.*Kata kunci : Ascidia; keanekaragaman; indeks ekologi; pola distribusi